ANALISIS PENGARUH GAYA KEPEMIMPINAN TRANSFORMASIONAL DAN LINGKUNGAN KERJA NON FISIK TERHADAP KEPUASAN KERJA KARYAWAN PADA PT. PELABUHAN INDONESIA 1 ( PERSERO ) CABANG BELAWAN - Mawar Ningsih; Fauzia Agustini (Universitas Negeri Medan, 2018)
This study aims to identify and explain the Influence Influence Transformational Leadership Style and Non-Physical Work Environment The Job Satisfaction simultaneously and partially at PT Pelabuhan Indonesia I (Persero) Branch Belawan.This research was conducted at the office of PT Pelabuhan Indonesia I (Persero) Branch Belawan in the academic year 2014, with a population of 255 employees and a sample totaling 72 employees. Data collection techniques used were observation, and questionnaires. Reliability of the questionnaire using Cronbach Alpha test, and validity tested questionnaire with product moment correlation test. In this study, whole grains valid questionnaires. After the data were analyzed with SPSS 16, the obtained path analysis Y = 0.354 +0.600 x_1 x_2 +0.125. to determine the effect of independent variables on the dependent variable is the coefficient of determination with simultaneous use 87.5% with significant results using the F test. These results indicate that the influence of Transformational Leadership Style and Non-Physical Work Environment The Job Satisfaction of employees simultaneously at PT Pelabuhan Indonesia I (Persero) Branch Belawan of 87.5%. Effect of Transformational Leadership Style partially on employee job satisfaction was 12.5% significantly by using T test. Effect of Non-Physical Work Environment partially on employee job satisfaction significantly by 36.0% by using the test T. Thus the hypothesis of this study is accepted that there Pengeruh between Transformational Leadership Style and Non-Physical Work Environment Against Employee Satisfaction At PT Pelabuhan Indonesia I (Persero) Branch Belawan. Keywords: Transformational Leadership Style, Non-Physical Work Environment, Job Satisfaction.